2016
DOI: 10.1080/15265161.2016.1161404
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making in the Shadow of Death

Abstract: IntroductionIt is often assumed that decision-making is a completely rational process. In reality, of course, numerous heuristics and biases influence the way we think and the decisions we make in clinical, research and policy contexts. While Blumenthal-Barby elegantly describes various types of heuristics and biases, and the effect that they may have on one's autonomy, i we suggest that there is insufficient attention given to the heuristics that may be most determinative in medical contexts -hope, and its at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Patients, in particular those facing a high risk of death, are often highly cognizant of both the degree to which they are reliant on the expertise of healthcare professionals and institutions on which their survival depends, and of the ways in which their choices are determined by, and impact on, their families and friends. 4 This account of decision-making in high-risk situations is more consistent with feminist accounts of autonomy, which note the degree to which autonomy is 'relational' located socially and not simply within the individual. 5 While relational autonomy does not 'dull' the immediacy or the starkness of the choices faced by patients in high-risk situations, locating autonomy socially, rather than individually, and describing it in terms of the specific medical context in which it is actualised, better accounts for the ways in which every element of consent is compromised or challenged by illness.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Patients, in particular those facing a high risk of death, are often highly cognizant of both the degree to which they are reliant on the expertise of healthcare professionals and institutions on which their survival depends, and of the ways in which their choices are determined by, and impact on, their families and friends. 4 This account of decision-making in high-risk situations is more consistent with feminist accounts of autonomy, which note the degree to which autonomy is 'relational' located socially and not simply within the individual. 5 While relational autonomy does not 'dull' the immediacy or the starkness of the choices faced by patients in high-risk situations, locating autonomy socially, rather than individually, and describing it in terms of the specific medical context in which it is actualised, better accounts for the ways in which every element of consent is compromised or challenged by illness.…”
mentioning
confidence: 59%
“…While philosophical accounts of autonomy have traditionally focused on sovereignty and rationality, when faced with death patients are intensely vulnerable and they may become more concerned with their care and their future than their ‘power’ or independence. Patients, in particular those facing a high risk of death, are often highly cognizant of both the degree to which they are reliant on the expertise of healthcare professionals and institutions on which their survival depends, and of the ways in which their choices are determined by, and impact on, their families and friends . This account of decision‐making in high‐risk situations is more consistent with feminist accounts of autonomy, which note the degree to which autonomy is ‘relational’ – located socially and not simply within the individual…”
mentioning
confidence: 94%
“…The authors suggest that instead of informed consent, clinicians offer their commitment to providing the support that patients and caregivers need during throughout the transplant process. Similarly, Scanlan et al 37 proposed that informed consent for BMT is more about building a trusting relationship than about education. As the participants’ solutions in this study emphasized, there is potential for ongoing interaction with the clinical team, particularly in the pre-BMT period, to have an impact on patient and caregiver experiences later in transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study of HCT recipients, their significant others and healthcare professionals caring for them, 3 we found that, almost without exception, patients had decided to proceed to HCT before they had met with the transplant team, or received any information about the transplant; that patients' decisions were deeply shaped by, and enmeshed in, their existing relationships and social roles; and that the process of information transfer served principally to establish trust and to reassure the patient, their family and the transplant team that HCT was appropriate and that it has a chance of success.…”
mentioning
confidence: 99%